Charismatic leadership through the eyes of followers. Issue 1 (2014) - ,; ,
Abstract : Purpose – The purpose of this paper is to try and explain what charismatic leadership might be, by finding out more about the other side of the relationship, the perspective of followers and their attitudes, feelings and responses to leaders.Design/methodology/approach – The authors examined followers' implicit narratives of their lived experiences of charismatic leadership in organizational settings and examined metaphors for this experience.Findings – Most respondents identified with positive affect, a form of love story; a minority experienced negative affect, especially anger; and some experienced both positive and negative emotions. The authors suggest that if one adopts a certain identity within the context of a dramatic narrative, one might be attributed with charismatic qualities by followers. In this way, it is suggested that charismatic leadership might be less a "gift from God" and more a "gift from followers".Originality/value – Most existing research on charismatic leadership has an essentialist orientation that characterizes it as leader behavior, leader communication or follower dependency. The authors' approach is more discursively oriented. To research charismatic leadership, aesthetic narrative positivism was used, which undertook utilitarian as well as critical method.